Fundamental factors of long-term criteria and selection of children at the first stage of multi-year sports training in gymnastics and dance sports - Луценко, Лариса; Артемьева, Галина; Чичкунова, Мария (Slobozhanskyi Herald of Science and Sport, 2017)
Larysa Lutsenko, Galyna Artemyeva & Mariia Chichkunova Purpose: to determine objective methods of selection and vocational guidance of children 6–7 years of age for practicing acrobatic rock’n’roll. Material & Methods: studies were conducted on a contingent of children Sports School No. 13 in the amount of 125 people. To write this work, the following research methods were used: pedagogical observation, medical and biological methods of assessing physical development, methods of mathematical statistics. Results: results of the conducted studies and the analysis of many years of experience with the children’s contingent engaged in acrobatic rock and roll allowed to generalize the features of the physical development of children and their success in mastering the arsenal of motor actions from the preparatory complex of physical exercises, available for a given age; to systematize the constitutional features of a child’s somatotype and a specific group of physical exercises that are more successfully mastered by them; to establish the priority of the motor qualities that are inherent in performing complex coordinated actions of a certain group of physical exercises in acrobatic rock’n’roll; set the compatibility condition for the possibility of complete sets of sports pairs. Conclusion: determining factor for the successful development of a specialized type of motor activity, characteristic of competitive exercises in gymnastic and dance sports, are the phylogenetic features of individual physical development.